Response Surface Optimization Of Banana (Musa Sp.) Fruit Juice Clarification Using Multi-Enzyme System (Pectinase, Cellulase And Hemicellulase) (Journal of Namibian Studies : History Politics Culture, 2023)
This study was carried out with an objective of producing high quality clarified banana juice with high yield by multienzyme treatment. Banana juice was treated with various concentration levels of commercial enzymes pectinase, cellulase and hemicellulase for different incubation periods. The effect of enzyme treatment conditions was studied on turbidity and yield of juice obtained from banana juice and optimum process conditions were determined. Response Surface Methodology (RSM) employing a second order central composite design was used to obtain optimum process conditions for simultaneous treatment with the range of variables for enzymatic treatment conditions giving the optimum values as 0.07%, 0.46% and 0.79% enzyme concentration for Pectinase, Cellulase and Hemicellulase respectively and incubation period of 123 min, at incubation temperature of 55 0C. Under this condition, the juice was obtained with turbidity value as 7 NTU and 79.5% of yield.